2018
DOI: 10.1371/journal.pone.0205794
|View full text |Cite
|
Sign up to set email alerts
|

What are the financial barriers to medical care among the poor, the sick and the disabled in the Special Administrative Region of China?

Abstract: Although Hong Kong is one of the richest cities in the world and has some of the best health outcomes such as long life expectancy, little is known about the people who are unable to access healthcare due to lack of financial means. Cross-sectional data from a sample of 2,233 participants aged 18 or above was collected from the first wave of the “Trends and Implications of Poverty and Social Disadvantages in Hong Kong” survey. Socio-demographic factors, lifestyle factors, and physical and mental health conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
18
2
Order By: Relevance
“…Detailed procedures had been described previously. [17][18][19][20][21] Of these respondents, 1855 in 2014 agreed to provide their contact numbers for participation in future research. Telephone survey was carried out from 20 April to 11 May 2020, during which the average daily number of incident case was 1.09.…”
Section: Respondents Were From a Previous Study Entitled 'Trends And mentioning
confidence: 99%
“…Detailed procedures had been described previously. [17][18][19][20][21] Of these respondents, 1855 in 2014 agreed to provide their contact numbers for participation in future research. Telephone survey was carried out from 20 April to 11 May 2020, during which the average daily number of incident case was 1.09.…”
Section: Respondents Were From a Previous Study Entitled 'Trends And mentioning
confidence: 99%
“…All children from age 10 to 17 from each sampled household were invited to complete the PDCW questionnaire. The sampling procedure of the first wave of the Living Standards Survey has already been described in detail elsewhere (Chung et al, ; Lau & Bradshaw, ; Wong et al, ). The second wave of this survey reinterviewed the first wave survey respondents between February 2016 and March 2017.…”
Section: Methodsmentioning
confidence: 99%
“…A local randomized controlled trial showed a significantly lower uptake of diabetic retinopathy screening among diabetic patients when a small co-payment is applied [55], whereas another local study reported that lower socioeconomic status was associated with a delayed detection of breast cancer [56]. Therefore, the disadvantaged tend to be excluded from the private sector which provides timely first-contact but more costly outpatient care as well as follow-up consultations for disease management [57].…”
Section: Economic Factor: Wealth Inequalitymentioning
confidence: 99%
“…Although a fast track is offered to urgent and more severe cases in the public sector, its limited capacity relative to the demand would inevitably lead to delay or even forgoing of medical consultations among the disadvantaged [6]. In fact, up to 8.4% of a cross-sectional general Hong Kong population sample reported that they did not seek medical care due to lack of financial means during the past year [57]. To alleviate the burden in the public sector, the Government has recently initiated public-private partnerships (PPP) so as to ensure efficient use of existing healthcare resources by subsidizing the worse-off to purchase private services [58].…”
Section: Economic Factor: Wealth Inequalitymentioning
confidence: 99%